1968
DOI: 10.3758/bf03330984
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of discrimination reversal learning in children

Abstract: Studies have repeatedly shown (Harlow, 1959) that the performance of infrahuman primates given single-object training trials with a nonrewarded object, the Negative (Neg) Stimulus, will, in subsequent two-choice discrimination trials, exceed that of animals given comparable training trials with a rewarded object, the Positive (Pos) Stimulus. This phenomenon has become known as the Moss-Harlow effect (Moss & Harlow, 1947), and the phenomenon lends support to a uniprocess, inhibition theory of discrimination lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
1975
1975

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Adults, in contrast, show effects of overlearning after 5 habitual trials (Grant & Berg, 1948), and it could be that 5-year-olds require fewer trials to arrive at a learning curve asymptote than infants, toddlers, and, 4-year-olds. For instance, Vaughter (1968) Jacques & Zelazo, 2005). If it were found that exposing children to more trials of the Matrix Sort Task prior to the Completion task improved performance, this approach could be utilized in interventions to help children perform better on concurrent cognitive flexibility tasks.…”
Section: Preschool Matrix Completion Taskmentioning
confidence: 99%
“…Adults, in contrast, show effects of overlearning after 5 habitual trials (Grant & Berg, 1948), and it could be that 5-year-olds require fewer trials to arrive at a learning curve asymptote than infants, toddlers, and, 4-year-olds. For instance, Vaughter (1968) Jacques & Zelazo, 2005). If it were found that exposing children to more trials of the Matrix Sort Task prior to the Completion task improved performance, this approach could be utilized in interventions to help children perform better on concurrent cognitive flexibility tasks.…”
Section: Preschool Matrix Completion Taskmentioning
confidence: 99%